1990
DOI: 10.1016/0014-5793(90)80059-r
|View full text |Cite
|
Sign up to set email alerts
|

High molecular weight forms of basic fibroblast growth factor recognized by a new anti‐bFGF antibody

Abstract: An antibody against basic fibroblast growth factor (bFGF) was raised using purified bovine pituitary bFGF. Western blot analysis revealed immunoreactive. bands at 18,24, 30-33 and 46 kDa in immunoaffinity purified extracts of pituitary and adrenal gland using this antibody. A similar staining pattern was obtained with ovary extracts with the exception of the missing 18 kDa band. A second anti-bFGF antibody raised against a synthetic peptide comprising the 24 N-terminal amino acids of bFGF reacted with the 18 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

1990
1990
1998
1998

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 21 publications
2
24
0
Order By: Relevance
“…In the growing postnatal testis of the rat, the Sertoli cell apparently is able to produce a bFGF-related factor, as concluded from in vitro experiments with isolated Sertoli cells from immature rats (4,7). In the present study we have shown expression of a 30-kDa bFGF-like protein in germ cells of the adult testes of two rodent species, rat and mouse, and, in addition, in the immature rat testis, using a recently characterized, highly specific antiserum against bFGF (8,9).…”
supporting
confidence: 72%
See 2 more Smart Citations
“…In the growing postnatal testis of the rat, the Sertoli cell apparently is able to produce a bFGF-related factor, as concluded from in vitro experiments with isolated Sertoli cells from immature rats (4,7). In the present study we have shown expression of a 30-kDa bFGF-like protein in germ cells of the adult testes of two rodent species, rat and mouse, and, in addition, in the immature rat testis, using a recently characterized, highly specific antiserum against bFGF (8,9).…”
supporting
confidence: 72%
“…Several higher mol wt forms (ranging from 20-25 kDa) have been described so far (13)(14)(15), and a number of less well characterized bFGFimmunoreactive proteins with higher molecular masses (including 24-, 27-, 29-, 30-, and 46-kDa forms) have been reported by various groups (8,9,(16)(17)(18). Interestingly, a 29-kDa form of bFGF was the predominant form in the pituitary and various brain regions of the rat (17).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Bohlen and Baird), and has been frequently characterized (see Blottner et al, 1989;Gonzalez et al, 1990;Grothe et al, 1990;1991b Specificity controls were carried out by 1) adsorbing the antibody to an excess of purified human recombinant FGF-2 (generous gift from PROGEN, Heidelberg, Federal Republic of Germany), 2) omitting the first antibody, or 3) replacing it with normal rabbit serum (cf. Grothe et al, 1991b).…”
Section: Methodsmentioning
confidence: 99%
“…The characteristics of the polyclonal anti-FGF-2 antibody were described earlier (Grothe et al 1990). In brief, the antiserum was generated in rabbits immunised against purified bovine pituitary FGF-2.…”
Section: Antibodiesmentioning
confidence: 99%